Geniekult in Geisteswissenschaften und Literaturen um 1900 und seine filmischen Adaptionen - Köhne, Julia Barbara (2014)
The monograph focuses on the "genius" as a figure of knowledge and representation in two discoursive and medial settings: first, texts from the Humanities and theory of science, in particular published between 1890 and 1920, and, second, subset feature films since the mid-1980ties, which re-echo the 'cult of the genius'. The "genius" is considered to be a figure by which newly constituted academic disciplines managed to build up their professional identity, legitimated their methodologies, and reassured themselves of their own intellectual and creative powers. Furthermore, the book shows how imaginations of "ingenious" artists and masterminds, that refer to this historical period, are depicted in selected movies since the mid 1980ties.